Hubungan Antara Psychological Capital Dan Work Engangement Karyawan Generasi Y di PT. Hadji Kalla (Holding) Makassar - Nursakinah, Jysa; Lukman; Andi Nasrawaty Hamid (CV. Ulil Albab Corp, 2025)
Generation Y, which currently dominates the labor market, has a low level of work engagement. This study aims to examine the relationship between psychological capital and work engagement among Generation Y employees. The participants in this study were Generation Y employees at PT. Hadji Kalla (Holding) in Makassar City (N=102). The sampling technique used in this study was purposive sampling. The measurement instruments used were an adapted version of the PCQ-24 scale and the UWES-17 scale. Data analysis was conducted using Spearman’s Rho correlation analysis. The results of this study indicate a significant relationship between psychological capital and work engagement (p=0.000, r=0.768). This study illustrates that the higher the psychological capital, the higher the work engagement among employees. The implication of this study for companies is that to enhance the work engagement of Generation Y employees, it is recommended to identify and develop employees' psychological capital by focusing on its four dimensions: self-efficacy, hope, resiliency, and optimism.